A prospective multicentric study of risk-reducing salpingo-oophorectomy in BRCA mutation patients: Risk-reducing salpingo-oophorectomy in BRCA mutations - Loizzi, Vera; Cicinelli, Ettore; Del Vecchio, Vittoria; Arezzo, Francesca; Deromemaj, Xheni; Kardhashi, Anila; Paradiso, Angelo; Legge, Francesco; Natalicchio, Maria Iole; Resta, Leonardo; Resta, Nicoletta; Loconte, Daria Carmela; et al. (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work: BRCA1/2 are tumour-suppressor genes involved in DNA homologous recombination and ovarian cancer development.  The study evaluated the risk of tumor cancer in women presenting the BRCA mutations.Methods: Risk-reducing surgery (RRS) was performed in 100 patients carrying BRCA1 (aged between 30-73 years, median age was 51 years) and BRCA 2 mutation (aged between 36-70 years, median age was 53 years). Fifty-eight patients had previous history of breast cancer.Results: Between the 100 patients, 82 women underwent risk-reducing salpingo-oophorectomy (RRSO) through a laparoscopic minimally invasive approach, 7 (7 %) underwent laparoscopic RRSO and contextual hysterectomy, 1 woman (1 %) underwent RRSO through a laparotomic approach and 10 women (10 %) laparotomic RRSO and hysterectomy. During 5 (5 %) laparoscopic RRSO, prophylactic bilateral mastectomy was also performed. Early and late complication occurred in 3 patients (3 %). Two patients (2 %) were found to have occult Serous Tubal Intraepithelial Carcinoma (STIC) and three patients (3 %) occult cancer.Conclusions: RRSO is safe and feasible in BRCA mutation carriers. The procedure is effective for genetic prevention of ovarian cancer.